The Water Wars Novel - Hannah Boast (Humanities, 2020)
‘Water wars’ are back. Conflicts in Syrian, Yemen and Israel/Palestine are regularly framed as motivated by water and presented as harbingers of a world to come. The return of ‘water wars’ rhetoric, long after its 1990s heyday, has been paralleled by an increasing interest among novelists in water as a cause of conflict. This literature has been under-explored in existing work in the Blue Humanities, while scholarship on cli-fi has focused on scenarios of too much water, rather than not enough. In this article I catalogue key features of what I call the ‘water wars novel’, surveying works by Paolo Bacigalupi, Sarnath Banerjee, Varda Burstyn, Assaf Gavron, Emmi Itäranta, Karen Jayes and Cameron Stracher, writing from the United States, India, Canada, Israel, Finland and South Africa. I identify the water wars novel as a distinctive and increasingly prominent mode of ‘cli-fi’ that reveals and obscures important dimensions of water crises of the past, present and future.